2008
DOI: 10.1021/bi7004152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metal Binding in the Active Sites of Acireductone Dioxygenase Isoforms from Klebsiella ATCC 8724

Abstract: The two acireductone dioxygenase (ARD) isozymes from the methionine salvage pathway of Klebsiella ATCC 8724 present an unusual case in which two enzymes with different structures and distinct activities towards their common substrates (1,2-dihydroxy-3-oxo-5-(methylthio)pent-1-ene and dioxygen) are derived from the same polypeptide chain. Structural and functional differences between the two isozymes are determined by the type of M +2 metal ion bound in the active site. The Ni +2 -bound NiARD catalyzes an off-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…(before Ni(Fe)ARD activity was discovered by Pochapsky et al [1,12] for bacteria and plants). Interestingly, in the case of KoARD (Klebsiella oxytoca ARD, bacterial enzyme ARD) unlike MmARD, Ni-bound form has higer activity than Fe-KoARD [1].…”
Section: Role Of Supramolecular Nanostructures Formed Due To H-bondinmentioning
confidence: 98%
See 2 more Smart Citations
“…(before Ni(Fe)ARD activity was discovered by Pochapsky et al [1,12] for bacteria and plants). Interestingly, in the case of KoARD (Klebsiella oxytoca ARD, bacterial enzyme ARD) unlike MmARD, Ni-bound form has higer activity than Fe-KoARD [1].…”
Section: Role Of Supramolecular Nanostructures Formed Due To H-bondinmentioning
confidence: 98%
“…Specific structural organization of iron complexes may facilitate the following regioselective addition of activated oxygen to Acireductone ligand and the reactions leading to formation of methionine (and ethylene also). So, in the Unlike catalysis with Fe-ARD, mechanism of catalysis by Ni-ARD does not include O 2 -activation, and oxygenation of Acireductone leads to the formation of products not being precursors of methionine [1,11,12]. In our previous works, we have shown that formation of multidimensional forms based on nickel complexes can be one of the ways of regulating the activity of two enzymes [4].…”
Section: Role Of Supramolecular Nanostructures Formed Due To H-bondinmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5 ppb indium solution (in 2% HNO 3 ) was used as the instrument internal standard during the runs. Isotopes 24 Mg, 55 Mn, 57 Fe, 59 Co, and 60 Ni were quantitatively monitored in a peak hopping mode with a total of 100 scans per point per isotope (50,000 s of dwell time and five replicates of 20 scans).…”
Section: Ard1-gfp Transient Expression In Arabidopsis Protoplasts-mentioning
confidence: 99%
“…Both these forms of ARD have been isolated from native K. oxytoca (Myers et al, 1993), and are also obtained upon overexpression in Escherichia coli. The activities of the two enzymes can be interconverted by replacement and reconstitution with the appropriate metal (Chai et al, 2008). These represent the only known pair of naturally occurring metalloenzymes with distinct functions determined solely by the metal ion identity in the active site.…”
Section: Introductionmentioning
confidence: 99%